UNDERSTANDING THE CONCEPT OF DIGITAL LITERACY AND INNOVATIVE WORK BEHAVIOR - Hani Maisarah Nasaruddin; Muhamad Aiman Najmi bin Zulkifli; Faris Harith bin Badrul Hisham Nasution; Nurazzaratul Arissa binti Ab Halim; Nur Zawani binti Zailudin (International Journal of Accounting, Finance and Business, 2022)
In the present circumstances, coronavirus disease (COVID-19), which limits the movement to go to work, has the potential to open up everyone's attention to the use of more technological innovations. Other than that, especially office employees use their abilities to adapt to these changes even though this new norm situation could not have physical touch. The presence of the virus COVID-19 that hinders movement is an issue. One of the difficult problems is acquiring the necessary digital literacy for success in employment. Therefore, this research aims to explore the concept of digital literacy and innovative work behavior in a workplace setting. This study provides a clear understanding of digital literacy, personal innovativeness, and individual innovative work behavior. In addition, the current study involves reviewed research articles that were gathered from Scopus, Science Direct, and Emerald databases. A total of 15 articles have been reviewed from the year 2017 to 2022. Based on the review, this study found that employee digital literacy is on the rise due to the current changes in the modern era. In addition to that, past studies revealed that digital literacy is widely associated with innovative work behavior. This study's findings contribute to the body of literature on digital literacy and assist organizations in understanding the importance of digital literacy on organizational outcomes such as innovative work behavior and organizational performance. The digital literacy program will provide employees with the digital skills required to engage in innovative work behavior. Future studies are recommended to provide empirical evidence on the association between digital literacy and innovative work behavior.